Histatins, wound healing, and cell migration. (13th March 2018) - Torres, P; Castro, M; Reyes, M; Torres, VA
Abstract : Wounds in the oral mucosa heal faster and more efficiently than those in the skin, although the mechanisms underlying these differences are not completely clear. In the last 10 years, a group of salivary peptides, the histatins, has gained attention on behalf of their ability to improve several phases of the wound‐healing process. In addition to their roles as anti‐microbial agents and in enamel maintenance, histatins elicit other biological effects, namely by promoting the migration of different cell types contained in the oral mucosa and in non‐oral tissues. Histatins, and specifically histatin‐1, promote cell adhesion and migration in oral keratinocytes, gingival and dermal fibroblasts, non‐oral epithelial cells, and endothelial cells. This is particularly relevant, as histatin‐1 promotes the re‐epithelialization phase and the angiogenic responses by increasing epithelial and endothelial cell migration. Although the molecular mechanisms associated with histatin‐dependent cell migration remain poorly understood, recent studies have pointed to the control of signaling endosomes and the balance of small GTPases. This review aimed to update the literature on the effects of histatins in cell migration, with a focus on wound healing. We will also discuss the consequences that this increasing field will have in disease and therapy design.